1988
DOI: 10.3109/00498258809055133
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of nilvadipine, a new dihydropyridine calcium antagonist, in mice, rats, rabbits and dogs

Abstract: 1. The pharmacokinetics of nilvadipine in male and female rats, and in male mice, rabbits and dogs were studied after i.v. and oral dosing. 2. After i.v. dosing (0.1 mg/kg), the plasma concentrations of nilvadipine declined two- or three-exponential with terminal half-lives of 0.73 h in mice, 1.2 h in male and female rats, 3.7 h in rabbits and 5.0 h in dogs. Sex difference in pharmacokinetics after i.v. dosing in rats was not found. The systemic plasma clearance was in the order of mice greater than rats great… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…1 h in the dog) (9) or benidipine (0.5 and 1 . 1 to 1.5 h) (15); they were similar to nisoldipine (0.4 and 4.0 h) (I), nitrendipine (1.3 and 1.8 h) (17), felodipine (1.5 and 4.2 h) (2), or nilvadipine (1.3 and 5.0 h) (44). Amlodipine, a 1,4-dihydropyridine calcium antagonist, however, displayed a longer half-life in rats (3 h) and dogs (30 h) (37).…”
Section: Plasma Concentrationmentioning
confidence: 99%
“…1 h in the dog) (9) or benidipine (0.5 and 1 . 1 to 1.5 h) (15); they were similar to nisoldipine (0.4 and 4.0 h) (I), nitrendipine (1.3 and 1.8 h) (17), felodipine (1.5 and 4.2 h) (2), or nilvadipine (1.3 and 5.0 h) (44). Amlodipine, a 1,4-dihydropyridine calcium antagonist, however, displayed a longer half-life in rats (3 h) and dogs (30 h) (37).…”
Section: Plasma Concentrationmentioning
confidence: 99%
“…In fact, the mebudipine plasma concentration declined biexponentially. The plasma concentration of most dihydropyridines have shown bi or tri exponential decline [8,10,11,12,13]. Therefore, it is concluded that mebudipine is pharmacokinetically similar to other dihydropyridines.…”
Section: Resultsmentioning
confidence: 99%
“…The systemic clearance of most dihydropyridines is equal to or higher than the liver blood flow [10,11]. Benidipine [8], nisoldipine [12], nitrendipine [13], felodipine [8], nilvadipine [11] and lacidipine [10] have a higher systemic clearance than mebudipine after intravenous administration. When considering the CL of 1.67 l/h/kg, the systemic clearance of mebudipine is generally high and it seems that the main reason for the long half-life of mebudipine is a large volume of distribution (6.2 l/kg).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…17,18) Although these reports suggested that NiD was highly permeable drug in upper bowel, the permeability in distal bowel has not been clarified. Thus, regional difference in intestinal absorption of NiD was evaluated in dogs using in situ closed loop, by obtaining the decrease of NiD concentration in solution from duodenal, jejunal, ileal, and colonic loops.…”
Section: In Vivo Performance Of Dcmt In Fasted Dogsmentioning
confidence: 98%